Potential protective role of Bifidobacteria in myopia prevention: evidence from full-length 16S rRNA sequencing and bidirectional Mendelian randomization analysis - Tang, Guodong; Han, Yibo; Gong, Xiaoqi; Wang, Xuejing; Li, Jing; Zhang, Jun; Wang, Junru; Song, Jike; Bi, Hongsheng (Frontiers in Medicine, 2025)
IntroductionThe increasing prevalence of myopia worldwide poses significant public health concerns. Accumulating evidence suggests a potential link between ocular diseases and the gut microbiota (GM); however, whether the GM directly contributes to myopia development remains to be established.MethodsThis study investigated the potential causal link between the GM and myopia through bidirectional Mendelian randomization (MR) analysis, further validated by experiments conducted on a form-deprivation myopia (FDM) guinea pig model. Bidirectional two-sample MR analysis was performed using genome-wide association study summary statistics comprising data on 196 GM taxa from the MiBioGen consortium and myopiaassociated data from the FinnGen database. Instrumental variables were carefully selected according to predetermined standards. Subsequently, MR estimates were calculated using the inverse variance weighted, MR-Egger regression, and weighted median approaches, along with supplementary sensitivity evaluations. Concurrently, FDM was experimentally induced in guinea pigs, and fecal samples were subjected to comprehensive full-length 16S rRNA gene sequencing analysis.ResultsMR analysis identified five bacterial taxa linked to the risk of myopia. Specifically, higher Bifidobacterium abundance was associated with lower myopia risk (odds ratio = 0.834, 95% confidence interval = 0.705–0.986, p < 0.05). Animal experiments validated the MR findings, demonstrating a significant enrichment of Bifidobacteria in control animals.DiscussionConclusively, supplementation with Bifidobacteria is a potential strategy for reducing the risk of myopia. Future research should focus on developing and testing Bifidobacterium-based interventions to validate their effectiveness in controlling myopia.